Analisis Daerah Rawan Bencana Kekeringan Berbasis Sistem Informasi Geografis di Kabupaten Bondowoso Provinsi Jawa Timur - ARDIANSYAH, WAHID; NUARSA, I WAYAN; BHAYUNAGIRI, IDA BAGUS PUTU (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
Analysis of Drought-Prone Areas Based on Geographic Information Systems in Bondowoso Regency, East Java Province Hydrometeorological disasters that often hit Indonesia are floods in the rainy season and drought in the dry season.  The plains in Bondowoso Regency consist of mountains and hills covering 44.4%, highlands covering 24.9%, and lowlands covering 30.7% of the total area. Such land conditions in Bondowoso Regency have a negative impact on another aspect, namely the availability of clean water for the surrounding community. This study aims to determine the distribution of drought-prone areas in the Bondowoso Regency, verify the results of the analysis with BPBD data from Bondowoso Regency, and directions for drought mitigation. The method used in this research is spatial analysis with a scoring system using Quantum GIS software. The results showed that in Bondowoso District, there are 5 classes of drought susceptibility.  Those classes including a very low drought hazard class covering an area of ??0 ha, a low hazard class with an area of ??928 ha, the moderate hazard class with an area of ??73,378 ha, the high hazard class with an area of ??77,522 ha, and a very high with an area of ??4,172 ha.